The News Coverage of the Islamic Defenders Front (FPI) Ban in Indonesian Print Media - Eka Nada Shofa Alkhajar; Sri Herwindya Baskara Wijaya; Pawito Pawito; Hamid Arifin; Firdastin Ruthnia Yudiningrum (LPPM Universitas PGRI Adi Buana Surabaya, 2021)
In late 2020, the Indonesian government has decided to ban the Islamic Defenders Front (FPI) and its activities. The ban was based on a joint decree (SKB) issued by six officials, i.e.: Minister of Home Affairs, Minister of Legal Affairs and Human Rights. Minister of Communications and Informatics, Attorney General, Indonesian National Police Chief, and National Counterterrorism Agency Head. The ban has caught the attention of Indonesian people, including being the subject of news in various media, i.e.: print, electronic and online. This research aims to examine the news coverage of the FPI ban in the selected Indonesian print media. This research used the qualitative content analysis method. The results found that there were some differences between the selected Indonesian print media in their news coverage practices.